Fly-ash based geopolymer mortar for high-temperature application – Effect of slag addition. (20th September 2021) - Hager, Izabela; Sitarz, Mateusz; Mróz, Katarzyna
Abstract: Geopolymers are used as a Portland cement alternative in some applications. The motivation for using geopolymers is their capacity of the by-products and waste incorporation, contributing to a cleaner environment. The present study aims to evaluate the impact of temperature exposure (up to 1000 °C) on the microstructure and the mechanical properties of the geopolymer mortars. Four mixes were investigated with fly ash as the main precursor with four levels of slag replacement 0, 10, 30, and 50 wt%. To evaluate damage evolution, mechanical performances and identification tests were performed: ultrasonic pulse velocity, scanning electron microscope, mercury intrusion porosimetry, thermal strains measurements, differential thermal analysis and thermogravimetry. The research aimed to develop a mortar composition that is thermally stable at high temperature. Although slag addition improves the mechanical performances of fly ash geopolymer mortar considerably (compressive strength above 100 MPa), the mortar with no slag addition yielded better performances at high temperature. In this study, manufactured mortars exhibited a 30% strength increase and doubled tensile strength at 200 °C. Moreover, for developed mixes, a compressive strength recovery of up to 90% at 1000 °C was observed, demonstrating the potential of fly ash geopolymer as high-temperature application material. Highlights: Slag addition to fly-ash geopolymer mortar ensures that it sets at ambient temperature, and its compressive strength may reach 100 MPa. Unblended fly-ash geopolymer yield better performance at higher temperatures due to geopolymerisation progress, sintering effect and uncracked matrix structure. After temperature exposure, the geopolymer with no slag addition showed more stable mechanical performances. High endothermic peak at 80 °C of unblended fly–ash geopolymer is a favourable feature of passive fire protection materials.